Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

The equation (x – 2)² + 1 = 2x – 3 is a (a) linear equation (b) quadratic equation (c) cubic equation (d) bi-quadratic equation

The equation (x – 2)² + 1 = 2x – 3 is a
(a) linear equation
(b) quadratic equation
(c) cubic equation
(d) bi-quadratic equation

Grade:12th pass

1 Answers

Pawan Prajapati
askIITians Faculty 8740 Points
4 months ago
Answer: b Explaination:Reason: We have (x – 2)² + 1 = 2x – 3 ⇒ x² + 4 – 2 × x × 2 + 1 = 2x – 3 ⇒ x² – 4x + 5 – 2x + 3 = 0 ∴ x² – 6x + 8 = 0, which is a quadratic equation.

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free